THE ROLE OF THE TEACHER IN THE INTEGRATIVE ORGANIZATION OF STUDENTS' LEARNING ACTIVITIES THROUGH "LANGUAGE PORTFOLIOS" (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The integration of language portfolios in students' learning activities has gained significant attention as an effective pedagogical tool. This study explores the role of teachers in the integrative organization of students' learning through language portfolios, emphasizing their impact on self-assessment, reflective learning, and autonomous development. The research highlights how teachers facilitate the use of language portfolios to enhance language competence and critical thinking skills among students. The study also examines the advantages of language portfolios in fostering motivation, self-directed learning, and communicative competence. The findings suggest that the teacher's role is crucial in structuring portfolio-based learning activities, guiding students in their learning progression, and providing constructive feedback. Through a review of existing literature and practical methodologies, this paper presents a comprehensive analysis of how teachers can optimize the implementation of language portfolios in pedagogical settings. The study aims to contribute to the understanding of portfolio-based education and its effectiveness in shaping students' linguistic and cognitive abilities.